VOICES OF TRANSFORMATION: UNVEILING WHITENESS, CULTIVATING EQUITY, AND FOSTERING DIALOGUE IN EDUCATION - Sidhu, Gurkirat; Bicknell-Hersco , Prilly (YU-WRITE: Journal of Graduate Student Research in Education, 2024)
This paper delves into the concept of collegial conversation within the context of education, emphasizing the need for a transformative dialogue among educators. The importance of meaningful conversations, characterized by substantial content, voluntariness, common ground, and evolutionary aspects over time, is highlighted. The narrative then shifts to a collegial conversation between two graduate studies professionals, Author One and Author Two, focusing on the experiences of racialized educators and students in the Ontario K-12 education system. The dialogue unveils the stark underrepresentation of racialized teachers, particularly in the context of the Peel District School Board (PDSB). The authors explore the impact of whiteness on both racialized students and educators, examining systemic issues within education that perpetuate racial oppression. Author One reflects on his journey as a French teacher, exposing the challenges of conforming to Eurocentric standards, while Author Two underscores the detrimental effects of a curriculum centered around white ideologies. The conversation advocates for a shift in responsibility from blaming families to addressing institutional inequities, ultimately emphasizing the crucial role of collegial conversations in fostering genuine understanding and dismantling systemic racism in education.